Genotypes, irrigation and fertility effects on seed yield, water use and water-use efficiency of spring sunflower (Helianthus annuus) - RAJ, BALDEV; SINGH, TEJ; SINGH, HARBIR (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during spring 1992 and 1993 to study the effect of irrigation and fertility levels on seed yield, water use and water-use efficiency of 2 sunflower (Helianthus annuus L.) cultivars on sandy loam soil. ’MSFH-8’ sunflower hybrid had significantly higher seed yield, higher water use and water-use efficiency compared to the composite’ EC 68415 C’. Seed yield of 1 737 kg/ha was obtained with irrigation scheduled at irrigation depth : cumulative pan evaporation of 0.4, which did not differ. significantly from that of 0.6; ID 60 mm. The lower yield was with crop irrigated at ID : CPE ratio of 0.2. An increase in irrigation frequency increased the seasonal water-use and decreased water-use efficiency. Application of 120 N + 60 kg p2 O5/ha resulted in higher seed and oil yield, water use and water-use efficiency. Interaction between genotypes, irrigation schedules and fertility levels was,however, observed to be non-significant